Randomized controlled trial of increasing physical activity on objectively measured and self‐reported cognitive functioning among breast cancer survivors: The memory & motion study. Issue 1 (19th September 2017) - Hartman, Sheri J.; Nelson, Sandahl H.; Myers, Emily; Natarajan, Loki; Sears, Dorothy D.; Palmer, Barton W.; Weiner, Lauren S.; Parker, Barbara A.; Patterson, Ruth E.
Abstract : BACKGROUND: Increasing physical activity can improve cognition in healthy and cognitively impaired adults; however, the benefits for cancer survivors are unknown. The current study examined a 12‐week physical activity intervention, compared with a control condition, on objective and self‐reported cognition among breast cancer survivors. METHODS: Sedentary breast cancer survivors were randomized to an exercise arm (n = 43) or a control arm (n = 44). At baseline and at 12 weeks, objective cognition was measured with the National Institutes of Health Cognitive Toolbox, and self‐reported cognition using the Patient‐Reported Outcomes Measurement Information System scales. Linear mixed‐effects regression models tested intervention effects for changes in cognition scores. RESULTS: On average, participants (n = 87) were aged 57 years (standard deviation, 10.4 years) and were 2.5 years (standard deviation, 1.3 years) post surgery. Scores on the Oral Symbol Digit subscale (a measure of processing speed) evidenced differential improvement in the exercise arm versus the control arm (b = 2.01; P < .05). The between‐group differences in improvement on self‐reported cognition were not statistically significant but were suggestive of potential group differences. Time since surgery moderated the correlation, and participants who were ≤2 years post surgery had a significantly greater improvement in Oral Symbol Digit score (exercise vs control (b = 4.00; P < .01), but no significant improvement was observed in patients who were >2 years postsurgery (b = −1.19; P = .40). A significant dose response was observed with greater increased physical activity associated with objective and self‐reported cognition in the exercise arm. CONCLUSIONS: The exercise intervention significantly improved processing speed, but only among those who had been diagnosed with breast cancer within the past 2 years. Slowed processing speed can have substantial implications for independent functioning, supporting the potential importance of early implementation of an exercise intervention among patients with breast cancer. Cancer 2018;124:192‐202 . © 2017 American Cancer Society . Abstract : Breast cancer survivors randomized to an exercise arm significantly improve on an objective measure of processing speed compared with a control arm, but only among those diagnosed with breast cancer within the past 2 years. Within the exercise arm, there is a significant dose response, with greater increases in physical activity associated with greater improvements in neurocognitive testing and self‐reported cognitive abilities.